2014
DOI: 10.1038/nature13548
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor structures reveal subunit arrangement and pore architecture

Abstract: Summary N-methyl-d-aspartate (NMDA) receptors are Hebbian-like coincidence detectors, requiring binding of glycine and glutamate in combination with the relief of voltage-dependent magnesium block to open an ion conductive pore across the membrane bilayer. Despite the importance of the NMDA receptor in the development and function of the brain, a molecular structure of an intact receptor has remained elusive. Here we present x-ray crystal structures of the GluN1/GluN2B NMDA receptor with the allosteric inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
623
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(651 citation statements)
references
References 67 publications
24
623
2
2
Order By: Relevance
“…This conclusion is also consistent with structural data showing that the LBD of GluA2 contains a number of zinc binding sites formed mainly by histidine residues (42). Because the ATD and LBD are tightly packed in NMDARs but more separated in AMPARs, with the consequence that the ATD is not a regulatory site for AMPARs (8,9), we propose that the LBD is a more likely site for allosteric AMPAR modulation by zinc. More studies are needed for determining the subunit sensitivity, the binding site, and the underlying biophysical mechanism of zinc-mediated AMPAR inhibition.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This conclusion is also consistent with structural data showing that the LBD of GluA2 contains a number of zinc binding sites formed mainly by histidine residues (42). Because the ATD and LBD are tightly packed in NMDARs but more separated in AMPARs, with the consequence that the ATD is not a regulatory site for AMPARs (8,9), we propose that the LBD is a more likely site for allosteric AMPAR modulation by zinc. More studies are needed for determining the subunit sensitivity, the binding site, and the underlying biophysical mechanism of zinc-mediated AMPAR inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…6 and 7]. Recent structural studies revealed that the amino terminal domain (ATD) and ligand-binding domain (LBD) are tightly packed in NMDARs but not AMPARs (8)(9)(10). These structural differences explain some of the functional differences in allosteric modulation between AMPARs and NMDARs, such as why the ATD of NMDARs, unlike that of AMPARs, modulates function and contains numerous binding sites for allosteric regulators.…”
mentioning
confidence: 99%
“…S2). Because the assembly of iGluR heterotetramers is mediated via a dimer of dimers organization (25,26,42) and coexpression of GluRIIA/E and Neto β induced small but significant currents, we speculate that the order of subunit arrangement in the Drosophila NMJ heterotetramers entails the formation of GluRIIA/E and the reciprocal C/D dimers. In Xenopus oocytes, surface expression of iGluR heterotetramers is much lower than that of vertebrate GluK2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3A), a position that in vertebrate GluA2 and GluK2 AMPA and kainate receptors is converted to an arginine by RNA editing (20)(21)(22). In the M3 helix, which forms the entrance to the ion channel pore in glutamate receptors (23)(24)(25)(26), Drosophila GluRIIB has three amino acid substitutions; most notable is the replacement of asparagine by lysine at position 647 (Fig. 3A).…”
Section: Efficient Receptor Expression and Function Requires Multiplementioning
confidence: 99%
“…Two major classes of transmembrane structures seen in tomograms at the PSD were originally designated as AMPAR-or NMDAR-type, respectively (3), based on the close match between the sizes and shapes of their electron-dense structure in the synaptic cleft and the extracellular domains at high-resolution structures of AMPA and NMDA receptors (64)(65)(66). The corresponding cytoplasmic sides of these two types of transmembrane structures in tomograms differed markedly in size and shape, consistent with the fact that C-terminal tails of NMDA receptors, especially GluN2 C tails, are much larger than those of any of the AMPAR subunits (3,4,37,67).…”
Section: Analysis Of Ampar-and Nmdar-type Structures By Em Tomographymentioning
confidence: 99%